Creating community on Twitter around a nonexistent medium, El Español - Doval-Avendaño, Montserrat (Estudios sobre el Mensaje Periodístico, 2017)
Nearly 4,000 messages on Twitter were analyzed and interviews were conducted with those responsible for the account management before and after the launch of the newspaper El Español in order to detect best practices in creating a community. Initially, the Twitter account effectively managed the expectation of a new medium and created a relationship with shareholders and subscribers. In the most recent period, El Español has given more importance to increasing traffic to its website than the relationship with potential subscribers. If we consider that El Español originally sought more subscribers than advertising, it seems that the management of the Twitter account in recent months is not consistent with that purpose.
Keywords: Twitter; crowdfunding; El Español.